PERBANDINGAN REGULASI: IMPLEMENTASI PERMENDAGRI DAN INMENDAGRI DALAM PERENCANAAN PEMBANGUNAN DAERAH - Dhea Candra Dewi; Nidya Putri Syahida; Vidya Yanti Utami (Nusantara Hasana Journal, 2025)
In the national development planning system as well as the regional  government system, a regulation is present as a guideline to facilitate the policy implementation process so that it can be  implemented properly. Regulation or development planning policy is one of the important instruments to ensure a directed, measurable and participatory development process. The purpose of this study is to compare two regulations that are the main points of reference in the regional development planning process. The research used is library research using written materials such as manuscripts, books, newspaper and other documents. And then compiled, analyzed using comparative content analysis techniques and the concluded. This study found that the comparison between the regulation of Permendagri 86/2017 and Inmendagri 2/2025 reflects that there is a shift in the regional development planning paradigm from a manual and decentralized to a digital and centralized approach. In additions, normatively the changes between these two regulations show high strategic effectiveness because they are in line with the direction of national development which encourages institutional improvement.